2014
DOI: 10.1007/s10875-013-9985-z
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of IgPro20, a Subcutaneous Immunoglobulin, in Japanese Patients with Primary Immunodeficiency Diseases

Abstract: PurposeIntravenous (IVIG) and subcutaneous (SCIG) immunoglobulin infusions are widely used for the treatment of patients with primary immunodeficiency (PID) worldwide. This prospective, multicenter, open-label, single-arm Phase III study evaluated the efficacy, tolerability, and safety of IgPro20 (Hizentra®; L-proline–stabilized 20 % human SCIG) in adult and pediatric Japanese patients with PID.MethodsPatients received three IVIG infusions at 3–4-week intervals followed by a dose-equivalent switch to weekly SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 18 publications
11
39
1
Order By: Relevance
“…A Phase III pivotal study of IgPro20 in Japanese patients with PID showed that weekly SCIG treatment with IgPro20 was effective in pediatric and adult patients and was tolerated well. 12 The results obtained concur with those seen in previous European 13 and North American 10 trials of IgPro20, suggesting that SCIG could be an alternative treatment opportunity in Japan. IgPro20 has recently been approved in Japan for the treatment of PID and secondary immunodeficiency.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…A Phase III pivotal study of IgPro20 in Japanese patients with PID showed that weekly SCIG treatment with IgPro20 was effective in pediatric and adult patients and was tolerated well. 12 The results obtained concur with those seen in previous European 13 and North American 10 trials of IgPro20, suggesting that SCIG could be an alternative treatment opportunity in Japan. IgPro20 has recently been approved in Japan for the treatment of PID and secondary immunodeficiency.…”
Section: Introductionsupporting
confidence: 86%
“…The cost-minimization analysis of IVIG and SCIG treatment was based on the fact that the efficacy of these 2 treatments was comparable, as reported previously 10,12,13 and this trial has confirmed that IgPro20 treatment resulted in equivalent serum IgG levels compared with previous IVIG treatment. 12 Cost-minimization analysis is an appropriate approach when alternative therapies have identical outcomes, but differ in costs. 21,22 Cost components that were identical between 2 arms were excluded, and we focused on difference of costs between each arm.…”
Section: Pharmacoeconomic Assessmentssupporting
confidence: 71%
See 1 more Smart Citation
“…Historically, lifelong treatment of these types of PID with immunoglobulin (Ig) through various routes (e.g., intravenous (IV), subcutaneous (SC), intramuscular) has been wellestablished and has been shown to decrease the incidence of infections in these patients [1][2][3][4][5][6][7][8][9][10]. Moreover, SCIg therapy has been shown through several studies to be effective, safe, and well-tolerated in patients with PID [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. SCIg therapy may be beneficial for patients who are poor candidates for IVIg, have poor venous access, or have recurrent systemic infusion-related reactions (i.e., headache, fever, chills, or myalgia).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly with children, difficult venous access can be a barrier to IVIg therapy. The results from several studies have shown that SCIg in children is feasible and safe [14,16,19,[21][22][23][24][25]. It is now generally accepted that repeated SCIg infusions result in lower systemic adverse effects such as headaches and joint pain occurring within 72 h of the SC infusion [9].…”
Section: Introductionmentioning
confidence: 99%